1999
DOI: 10.1038/sj.onc.1202989
|View full text |Cite
|
Sign up to set email alerts
|

cJun overexpression in MCF-7 breast cancer cells produces a tumorigenic, invasive and hormone resistant phenotype

Abstract: We have previously demonstrated decreased Jun/AP-1 activity in the breast cancer cell line MCF-7 when compared to normal or immortalized mammary epithelial cells. In this paper, we overexpress Jun in MCF-7 cells (MCF7Jun) and demonstrate that it results in diverse biologic and biochemical changes, which mimic those seen clinically in breast cancer. Overexpression of Jun causes signi®cant alterations in the composition of AP-1, decreased junB and increased fra-1 expression and results in an increased biologic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
152
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 190 publications
(164 citation statements)
references
References 39 publications
11
152
0
1
Order By: Relevance
“…We have found that AP-1 inhibition induced by TAM67 sensitizes MCF7 breast cancer cells to apoptosis when these cells are starved of serum (unpublished observation). Previous data results showing that reducing AP-1 activity in breast cancer cells caused increased cell death after treatment with UV light or cisplatin chemotherapy are consistent with these results (Sauter et al, 1999;Smith et al, 1999;Potapova et al, 2001).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We have found that AP-1 inhibition induced by TAM67 sensitizes MCF7 breast cancer cells to apoptosis when these cells are starved of serum (unpublished observation). Previous data results showing that reducing AP-1 activity in breast cancer cells caused increased cell death after treatment with UV light or cisplatin chemotherapy are consistent with these results (Sauter et al, 1999;Smith et al, 1999;Potapova et al, 2001).…”
Section: Discussionsupporting
confidence: 81%
“…The cyclin D1 and cyclin E mRNA level was measured by performing RPA. TAM67 decreased the expression of cyclins mRNA including cyclin D's (a), but did not affect the expression level of cyclin E mRNA (b) Smith et al, 1999), chemotherapy resistance (Potapova et al, 2001), and tamoxifen resistance (Schiff et al, 2000). We have also shown that AP-1 blockade induced by TAM67 suppresses AP-1 activity induced by different peptide growth factors, including EGF, IGF-1, heregulin-b, b-FGF, and estrogen.…”
Section: Discussionmentioning
confidence: 99%
“…E-cadherin inactivation mechanism and EMT in breast cancer M Lombaerts et al proliferation, malignant transformation and aggressiveness of cells (Mechta et al, 1997;Smith et al, 1999). Detectable FOSL1 protein expression in mammary carcinomas was demonstrated to be associated with poor differentiation, Ki67 and cyclin E expression and an oestrogen receptor-negative phenotype (Milde-Langosch et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Besides the standard indicators of oncogenicity, such as multilayered growth on solid substrates, growth in low serum concentrations, anchorage-independence, and tumorigenicity, Jun also induces more subtle changes. Jun-expressing cells show increased motility and invasiveness Smith et al, 1999). In mammary epithelial cells, Jun induces the loss of polarity accompanied by a dissociation of beta-catenin from E-cadherin, redistribution of beta-catenin and a disruption of intercellular junctions (Fialka et al, 1996).…”
Section: The Jun Phenotypementioning
confidence: 99%
“…Formally, this is a co-transformation but Jun and Fra-1 probably form AP-1 dimers which qualify as a single oncogenic e ector. Overexpression of c-Jun greatly enhances the tumorigenic properties of the MCF7 human mammary carcinoma cell line, inducing elevated motility, unresponsiveness to estrogen and tamoxifen, and increased tumor formation in nude mice (Doucas et al, 1991;Smith et al, 1999). v-Jun can transform the mouse ®broblast cell line C3H10T1/ 2 (Cohen et al, 2001).…”
Section: Solo-transformationsmentioning
confidence: 99%